IMAJI BIBLIKAL SEBAGAI PENGHAYATAN IMAN PERSONAL DALAM PUISI-PUISI MARIO F. LAWI DAN RELEVANSINYA BAGI PEWARTAAN MELALUI KARYA SASTRA (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
Mario F. Lawi is one of the most popular young poet in the Indonesian Literary. He is well-known as the “biblical poet” who constantly explores biblical theme in a large number of his poems. This research elaborates biblical imagination as a form of a personal living faith and finds its relevance to the kerygmatic-preaching by the literature. This analysis uses the combination of three theories, i.e: the theory of intertextual semiotics by Michael Riffaterre from literature perspective, the theory of theological aesthetics by Hans Urs von Balhtasar from theology perspective and the concept of the kerygmatic-preaching from “The Letter of His Holiness Pope John Paul II to the Artists” by kergygmatic-preaching perspective. The result of this qualitative research i.e: 1) All of the biblical imagination in Mario’s poems have their references or allusions from the Bible text as their hipogram, 2) By theological aesthetics perspective, biblical imagination which is used by Mario in his biblical poems could be considered as a personal living faith, 3) The biblical imagination in Mario’s poems gives an altenative relevance to the kerygmatic-preaching ad intra (to the Christian readers) and ad exrtra (to the non-christian readers).